2021
DOI: 10.1021/acs.jpcc.1c04312
|View full text |Cite
|
Sign up to set email alerts
|

Tribovoltaic Device Based on the W/WO3 Schottky Junction Operating through Hot Carrier Extraction

Abstract: The tribovoltaic devices have demonstrated an enormous current density output from friction. This has attracted attention, and thus, the tribovoltaic device research is expected to grow rapidly, providing mechanical energy harvesting from human motion or mechanical vibrations to power the microdevices. Herein, we are demonstrating the novel tribovoltaic device based on the W/WO 3 Schottky junction enabled by high-energy electrons as in hot-carrier photovoltaic devices. The hot carrier injection from the metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Recently, tribovoltaic devices based on W/WO 3 Schottky junction was proposed to improve the lifetime of TVNG with the value of >1000 cycles. [ 29 ] TVNG based on MXene‐silicon heterojunctions was proposed, which can reach a high output peak current of 22 µA, as well as the enhanced lifetime of over 1800 cycles. [ 30 ] In addition, macro‐superlubric TVNG can operate stably for nearly 10 000 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, tribovoltaic devices based on W/WO 3 Schottky junction was proposed to improve the lifetime of TVNG with the value of >1000 cycles. [ 29 ] TVNG based on MXene‐silicon heterojunctions was proposed, which can reach a high output peak current of 22 µA, as well as the enhanced lifetime of over 1800 cycles. [ 30 ] In addition, macro‐superlubric TVNG can operate stably for nearly 10 000 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The tribo-thermoelectric and tribovoltaic coupling effect has also been reported by rubbing a metal on a semiconductor. ,, The friction induces electron–hole pairs, as well as generates heat, which drives the carrier to move from the hot side toward the cold side. We have also demonstrated that hot electrons from contact friction may play a role in metal–semiconductor TV devices …”
Section: Introductionmentioning
confidence: 87%
“…In TV devices, conductors (metals, degenerated semiconductors, or carbon) and semiconductors (Si, , MoS 2 , , perovskite, TiO 2 , ZnO, WO 3 , and others , ) are slid or dragged across each other, generating charge from interfacial friction.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon was also observed in tribovoltaic effect experiments of zinc oxide and tungsten oxide. [26,29] Moreover, the open-circuit voltage output of the SDC-TENG far exceeds that limited by the semiconductor bandgap. Previous mechanisms based on the built-in electric field and energy band theory have been difficult to be explained.…”
Section: Structure and Electric Output Characteristics Of Pbi 2 Te 3 ...mentioning
confidence: 99%
“…When the friction area is in the micro-or nanoscale, the SDC-TENG has ultrahigh current density (10 4 to 10 8 A m −2 ). [15,[20][21][22][23][24][25][26][27][28][29][30][31] A high power density (1000 W m −2 ) can be achieved under both a high velocity and a strong normal force. However, the actual output power of the SDC-TENG could not increase linearly with increasing area.…”
Section: Introductionmentioning
confidence: 99%